ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. “E” UMUR 24 TAHUN DI POLINDES MELATI BIDAN “N” DESA TUGUSUMBERJO KABUPATEN JOMBANG - Nanda Yuliana; Najah Soraya Niah; Rista Dian Anggraini (Library Unit of the College of Health Science Husada Jombang, 2023)
Introduction: The National Maternal Mortality Rate is 305 per 100,000 live births. In 2019, the Maternal Mortality Rate for East Java Province reached 89.81 per 100,000 live births. This figure has increased compared to 2020 which reached 98.39 per 100,000 live births. The most common causes of maternal death in Indonesia in 2019 are bleeding, hypertension in pregnancy, infections, metabolic disorders, and others (RI Ministry of Health, 2019). Around 25-50% of maternal deaths are caused by problems related to pregnancy, childbirth and the puerperium (WHO, 2018). Objectives: The purpose of conducting this research is to provide Comprehensive Midwifery Care for Ny. E is 24 years old at the Melati Midwife Polindes